Leaf blight caused by Curvularia coicis on Chinese pearl barley (Coix chinensis) in Fujian Province, China. Issue 2 (3rd April 2019) - Dai, Yu-Li; Gan, Lin; Chen, Fu-Ru; Yang, Xiu-Juan
Abstract: Chinese pearl barley ( Coix chinensis Tod.) is grown worldwide as a cereal food and medicinal plant. During 2016 and 2017, a severe leaf blight outbreak was observed in Nanjing prefecture, Fujian Province, China. The disease outbreak affected almost 100% of the Chinese pearl barley plants under field conditions. The pathogen was isolated from infected leaves showing typical symptoms of dark brown spots surrounded by yellow halos, and was identified as Curvularia coicis Castellani based on morphological characteristics and sequencing of the ribosomal DNA internal transcribed spacer (rDNA-ITS). The optimal temperature for mycelial growth of C. coicis on potato dextrose agar (PDA) ranged from 25°C to 28°C. Pathogenicity assays were performed using Chinese pearl barley 'Longyi 1' at the seven- to eight-leaf stage. Overall, C. coicis had a high virulence on these inoculated plants, even in the absence of wounds, and the pathogen was successfully reisolated. The results from this study identified the causal organism of leaf blight on Chinese pearl barley.